Using medical terminology - Nath, Judi Lindsley (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2013)
'Using Medical Terminology, 2e is written to teach the language of medicine in an engaging and meaningful way by chunking information into manageable blocks of text and immersing learners into the language of medicine. By using medical terminology in context, students will be prepared to enter the workforce. The number of exercises has expanded greatly, providing more opportunity to practice and review. The design for the second edition has been improved to make the text more appealing and much easier to use. The overall writing has been made even more student-friendly to help comprehension of medical terms without getting lost in scientific writing. The art program has been improved so that figure labels are less cluttered and include only those medical terms introduced in the chapter. The number of photographs has also increased significantly. Two new chapters, Oncology and Gerontology, have been included. In addition, former chapters 5 and 6, Skeletal System and Articulations, have been combined into one cohesive chapter, Skeletal System: Bones and Joints.'--Provided by publisher.
Machine generated contents note: Chapter 1. Introduction to Medical Terminology Chapter 2. Anatomical and Physiological Terminology Chapter 3. Radiology and Nuclear Medicine Chapter 4. Integumentary System Chapter 5. Skeletal System: Bones and Joints Chapter 6. Muscular System Chapter 7. Nervous System Chapter 8. Special Senses Chapter 9. Endocrine System Chapter 10. Blood Chapter 11. Cardiovascular System Chapter 12. Respiratory System Chapter 13. Lymphatic System and Immunity Chapter 14. Digestive System Chapter 15. Urinary System Chapter 16. Reproductive Systems Chapter 17. Pregnancy, Human Development, and Child Health Chapter 18. Mental Health Chapter 19. Pharmacology Chapter 20. Oncology Chapter 21. Gerontology.
Includes index.
Keywords: Terminology as Topic -- Problems and Exercises